FIDIC 2017 : a definitive guide to claims and disputes - Brown, Nicholas Alexander (Emerald Publishing Limited, 2025)
FIDIC 2017: A definitive guide to claims and disputes second edition serves as a practical legal companion for managing the procedures for claims and disputes within the 2017 FIDIC suite of contracts. It is the first book to present a comprehensive treatment of the multi-tiered dispute avoidance and resolution process. The book explains each stage of the process and includes numerous flowcharts and worked procedural examples to facilitate understanding. Fully revised and updated, this edition includes 2022 amendments to the FIDIC contracts and reforms to adjudication practice; worked procedural examples; provisions within the FIDIC Green Book (Second Edition 2021); recent court decisions and arbitral awards worldwide, and commentary on the World Bank's Standard Bidding Documents. Included in this definitive reference the distinct functions and powers of the Dispute Adjudication/Avoidance Board(DAAB) to avoid disputes techniques to achieve amicable resolution of claims and disputes full coverage of typical court enforcement powers and FIDIC's preferred arbitral procedure the operation of FIDIC contract provisions under a variety of civil, common law and mixed legal systems, drawing on court decisions and arbitral awards worldwide. FIDIC 2017: A definitive guide to claims and disputes second edition is an indispensable resource for professionals engaged with the FIDIC contracts. This comprehensive reference serves both construction professionals including engineers, surveyors and consultants as well as legal professionals including lawyers, adjudicators and chartered arbitrators.
Includes index.
Keywords: Business planning.; Customer relations.; Engineers.; Business & Economics -- Management.; Business studies: general.; Management and management techniques.; elektronické knihy; electronic books